Effectiveness of a scenario-based simulation course on improving the clinical communication skills of dietetic students - Mei-Yuan Liu; Li-Ling Liao; Yu-Ting Huang; Yi-Chen Lee; I-Ju Lai (BMC Medical Education)
Abstract Background Effective clinical communication skills are essential for dietitians as it impacts patient outcomes and satisfaction across diverse clinical and public healthcare settings. Despite its importance as a core competency, many dietetics programs, including those in Taiwan, need to provide sufficient training in this area. This study aimed to develop and assess a scenario-based simulation course to improve communication skills in dietetic students. Methods A non-randomized control group pretest–posttest design was used. The intervention consisted of a 12-week scenario-based simulation communication course divided into three units employing diverse teaching methods. One hundred nineteen third-year dietetic students from two universities were enrolled through convenience sampling, with 59 students in the experimental group and 60 in the control group. The experimental group participated in the course intervention, whereas the control group received no clinical communication skills training. Effectiveness was assessed by comparing participants' self-assessment of communication skills and Objective Structured Clinical Examination (OSCE) scores before and after the intervention and collecting feedback on learning satisfaction. Data were analyzed using paired t-tests and ANCOVA. Results The results showed that the post-test scores of the experimental group were significantly higher than those of the control group in terms of self-assessed clinical communication confidence, self-efficacy, and competence after controlling for pre-test scores. In the experimental group, the post-test OSCE scores were significantly higher than the pre-test scores, except for one item related to the nutrition assessment of diabetes. The intervention course's average learning satisfaction score was above 4.4 (out of 5 points). Conclusions This course effectively enhanced dietetic students’ clinical communication confidence, self-efficacy, and communication skills. These results can provide a reference for integrating clinical communication courses into undergraduate dietetics curricula.